A comprehensive review of cultural heritage integration in interior design - Li, Weifu; Mansor, Noranita; Mohd. Ali, Noor Azizi (Malque Publishing, 2024)
The preservation and transmission of cultural heritage products are urgent tasks for the global community in the face of the challenges of increasingly rapid modernization and urbanization. Interior design, as a practice capable of shaping spaces, environments and emotions, has the unique potential to preserve and transmit the importance of cultural heritage. However, few review articles have discussed the connections between them and the process of applying cultural heritage to interior design. Therefore, the aim of this review is to analyze the literature from October 2019 to 2023 on interior design related to cultural heritage. Articles from 3 leading databases (WOS, SCOPUS and ScienceDirect) were searched and screened. Forty-two articles that met the criteria were ultimately selected for comprehensive analysis. ATLAS.ti 23 was used as the analysis software to produce quantitative results reflecting trends in cultural heritage and interior design research. Moreover, six themes on the subject were obtained from the qualitative analysis: (1) Reuse of historic buildings; (2) Recycling of waste materials; (3) Heritage Elements for Interior Design; (4) Heritage values; (5) Challenges; and (6) Preservation methods. Finally, the findings are expected to help address the relationship between interior design and cultural heritage and provide insights for future research and practice on the sustainability of cultural heritage in interior design